Development of local food source products in improving the health of mother and toddler children in Jaharun B Village, Galang District, Deli Serdang District - bakara, tiar lince; Rumida; Siahaan, Ginta (Talenta Publisher Universitas Sumatera Utara, 2024)
Maternal and child health encompasses comprehensive efforts to maintain optimal health at every life stage, from pre-conception to menopause. Midwifery services play a crucial role in this system, focusing on women's reproductive health throughout their life cycle, as well as the health of infants and toddlers. Food and nutrition are essential for development and serve as key indicators of overall health. However, many children still experience nutritional deficiencies, often due to a lack of interest in protein-rich and vegetable-based foods. The aim of this Community Service initiative was to educate cadre groups and mothers of children under five on utilizing local food ingredients to create nutritious snacks. The program introduced innovative ways to process red bean flour, oyster mushrooms, and catfish into nuggets and meatballs, providing a protein-rich alternative for young children. The service was conducted in Jaharum B Village, Galang District, Deli Serdang Regency. Results indicated that participating mothers gained valuable knowledge about protein sources and acquired skills to prepare nutritious snacks from local ingredients. These efforts are expected to improve the nutritional intake of children under five, contributing to better community health outcomes.